ASME 2009 International Manufacturing Science and Engineering Conference, Volume 1 2009
DOI: 10.1115/msec2009-84235
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Micro Dent Arrays by Laser Shock Peening on Ti-6Al-4V Surfaces

Abstract: Surface micro dents may act as lubricant reservoirs to reduce friction and wear in sliding and rolling contact applications. Surface patterning has become a valuable technique for fabricating micro dents. Alternative methods such as micromachining present obvious limitations in comparison with laser shock peening (LSP). In this paper, the use of LSP along with an automatic X-Y table proves to be an attractive and reliable method for producing micro dent arrays with enhanced surface integrity and free of cracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Macropits were found at laser-impacted points. This phenomenon has been observed by many researchers [13][14][15][16]. However, more importantly, another extraordinary phenomenon was observed.…”
Section: Specimen Surface Morphology With Aluminum Foil Tape As Absormentioning
confidence: 55%
See 1 more Smart Citation
“…Macropits were found at laser-impacted points. This phenomenon has been observed by many researchers [13][14][15][16]. However, more importantly, another extraordinary phenomenon was observed.…”
Section: Specimen Surface Morphology With Aluminum Foil Tape As Absormentioning
confidence: 55%
“…Although we ideally hope that the mechanical performances of a laser-shock-processed (LSP'd) target will be improved without deteriorating its surface quality, the status of the surface do will be changed. As is well known, laser shock processing will create macropits on target surfaces, just as shot peening [13][14][15][16]. In recent years, some researchers have even used LSP to fabricate functional microdents on metal surfaces to improve the lubrication between friction pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile residual stress cannot be avoided due to the thermal nature of the LD process. Warren et al (2008) and Caslaru et al (2009) have used laser shock peening (LSP) to introduce deep subsurface compressive residual stress. Compressive residual stress is beneficial in improving fatigue life of metallic components and preventing stress corrosion cracking (Peyre et al, 2000).…”
Section: Recast Layer and Residual Stress Of Ldmentioning
confidence: 99%
“…It is demonstrated that LSP process utilizes the laser-shock-induced mechanical effect to improve both mechanical and physical properties of materials [10] . Caslaru et al [11] fabricated micro-dent arrays on Al6061-T6 surface by LSP and studied the effect of dent geometry on surface tribological performance. Guo et al [12] produced micro-dent arrays on the surface of Ti-6Al-4V via LSP.…”
Section: Locnzimentioning
confidence: 99%